Influence of Sports Camps and Vision on Perceived Motor Competence in Children and Adolescents who Are Visually Impaired. (September 2018) - Brian, Ali; Taunton, Sally; Haibach-Beach, Pamela; Lieberman, Lauren J.
Introduction: Children with visual impairments (that is, those who have low vision or blindness) often demonstrate lower levels of perceived and actual motor competence and physical activity compared to peers who are sighted. The purpose of this study was to assess the way in which seven-day sports camps specially designed for children with visual impairments affected perceived motor competence as compared to a control condition. Methods: Children with visual impairments (N = 79), ages 9 to 19 years (M = 12.71, SD = 2.38) completed either the Self-Perception Profile for Children (ages 9 to 13 years) or the Self-Perception Profile for Adolescents (ages 14 to 19 years) two to three times at two summer camps or at a school for blind students. Two separate 3 (group) × 4 (vision) ANOVAs assessed pretest and posttest differences for perceived motor competence. A 3 (group) × 2 (time) × 4 (vision) repeated-measures ANOVA examined the effects of camp on perceived motor competence from pretest to posttest. Paired samples t-tests were conducted to reveal if levels of perceived motor competence remained stable from posttest to maintenance. Results: Camp and control groups revealed nonsignificant and similar levels of perceived motor competence at the pretest. By the end of camp one, children improved their perceived motor competence to a much greater and significant degree than did those in the control condition. Similar effects occurred for those who enrolled at camp two, and those participants also revealed significantly greater gains than did those in the control group. A small subsample maintained their gains six weeks after camp one, while control children also remained stable with no change after six weeks. Discussion: Children's perceived motor competence can be improved through accessible sports camps. This finding is important, since this measure powerfully associates with physical activity. Implications for practitioners: Physical education teachers can model camp conditions to benefit perceived motor competence throughout the academic year.